Modernizing product development processes : guide for engineers - Quigley, Jon M.; Gulve, Amol D. (SAE International, 2023)
Product lifecycles have shortened due to competition, rapidly changing markets, emerging technology, and regulation. Modernizing Product Development Processes: Guide for Engineers provides a foundation to focus on giving engineers, entrepreneurs, and innovators a guide to developing products with a new approach instead of a traditional product development cycle. Using the fundamental pillars of this book, the authors demonstrate how to bridge the gap in today's product development cycle to improve "time to market" needs in a fast-paced environment. These pillars include: - Learning from failures and doing - Harnessing creativity (out-of-the-box thinking) - Front loading (develop concepts early) - Explore multiple possible solutions - Technology/Manufacturing readiness level - Modularity (integrate common solutions) In addition, the authors prepare engineers to scale up production to meet customer demands in a dynamic environment by demonstrating how to establish strategies and road maps with a stage gate approach focused on harnessing creativity to build concepts/technologies in early phases. In today's era of innovation, rapid technological growth, and high consumer demand, engineers must adapt and deliver products with reasonable, engineered solutions and this book shows them how.
Keywords: New products.; Technological innovations -- Management.; elektronické knihy; electronic books